Comparative analysis of the rate of aging young people of student age - Prikhodko S.I (Kharkov National Pedagogical University, 2012)
The problem of accelerated rates of aging of young people by the example of students. The data calculating biological age students on how Voitenko. Displaying discrepancy between passport and biological age boys and girls. 27 youths and 20 girls that study on 2 courses took part in research, on the state a health behave to the basic medical group. It is proved that the young men in the period of study have higher rates of aging. Found that young biological age than passport for 26 years, while the girls - at 11. It is used data of other authors to compare the biological age of students in different regions of Ukraine. It is recommended to give students information about their biological age and teach them to control this index during life.